Influence of Self-Efficacy on Affective Learning Outcomes in Social Studies Education Toward Achieving Sustainable Development Goals (SDGs) - Erlina Wiyanarti; Anisa Siti Nurjannah (ASEAN Journal of Educational Research and Technology, 2026)
This study aimed to investigate the influence of self-efficacy on affective learning outcomes in social studies education. The research employed a quantitative approach using a simple linear regression method with a sample of secondary school students. Data were collected through Likert-scale questionnaires validated for reliability and relevance. The findings revealed a significant positive relationship between self-efficacy and affective learning outcomes, especially in social behaviors such as honesty, responsibility, and cooperation. This relationship exists because self-efficacy supports students’ confidence and motivation, which in turn strengthens their social engagement and empathy during learning. The study highlights the importance of developing students’ internal psychological resources as part of educational efforts aligned with the Sustainable Development Goals, particularly those concerning quality education and social inclusion. The results suggest that enhancing self-efficacy can contribute to more holistic student development, integrating both academic success and character education for global citizenship.